2020
DOI: 10.29309/tpmj/2020.27.02.3537
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, types and treatment outcomes of Bile Duct Injuries (BDI) in laparoscopic cholecystectomy.

Abstract: Objectives: To study the types of Biliary injuries (BDIs), their timing and clinical presentation, diagnosis and treatment outcomes in patients undergoing laparoscopic cholecystectomy. Study Design: Descriptive study. Setting: Department of General Surgery Hayatabad Medical Complex (HMC) Peshawar. Period: From October 2017 to October 2018. Materials & Methods: including 32 patients with biliary duct injuries (BDIs). Results: This study included 32 patients with BDI, 28 patients were referred to HMC and 4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The study includes 50 patients undergone laparoscopic cholecystectomy and complicated by biliary duct injuries and Table (1) shows the descriptive data of 50 patients undergone L.C. complicated by BDI according to their sex as we got 31 females and 19 males with higher incidence with female sex as they are higher incidence for L.C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study includes 50 patients undergone laparoscopic cholecystectomy and complicated by biliary duct injuries and Table (1) shows the descriptive data of 50 patients undergone L.C. complicated by BDI according to their sex as we got 31 females and 19 males with higher incidence with female sex as they are higher incidence for L.C.…”
Section: Resultsmentioning
confidence: 99%
“…A study performed on 32 patients undergone laparoscopic cholecystectomy and complicated by bile duct injury and found that 12 patients presented by obstructive jaundice and 20 patients presented by bile leak, vomiting, abdominal pain and peritonitis, so increased incidence of obstructive jaundice than bile leak [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two most common complications after laparoscopic cholecystectomy contributing to 5-40% 5 cases are the bile leakage and stone spilling intraoperatively with lost stones frequency is not known much. Bile leakage due to rupture of gall bladder contributes to 7% -21.77% 4,5,7 according to most studies with conversion of laparoscopic into open cholecystectomy. Studies showed stone spillage with its retrieval from the fossa of gall bladder can be done by irrigation or be mopping with surgical gauze 7,8 .…”
Section: Introductionmentioning
confidence: 99%